2006
DOI: 10.1007/s10584-006-9052-3
|View full text |Cite
|
Sign up to set email alerts
|

Corrections of Systematic Errors, Data Homogenisation and Climatic Analysis of the Padova Pressure Series (1725-1999)

Abstract: A short history of the series with daily observations of barometric pressure in Padova (since 1725) is made, with special reference to the types of barometers used, their locations, the types of corrections (which were only partial in the early period), the calibrations and the comparison with primary instruments. The paper also describes the homogenisation of the series and the procedures used to fill the small gaps. The Padova series was compared with previously well investigated series from the ADVICE and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The WeMO was defined by MartinVide and Lopez-Bustins (2004, 2006 to account for those rainfall areas on the Iberian Peninsula which were not correlated with the NAOi. In addition, Camuffo et al (2006) recently used the WeMOi to compare it with variability in day-to-day pressure in Padova. In the study by Martin-Vide and Lopez-Bustins (2006), the WeMOi was shown to evolve in the opposite way to the AOi.…”
Section: Iberian Peninsula Winter Rainfall and Teleconnection Indicesmentioning
confidence: 99%
“…The WeMO was defined by MartinVide and Lopez-Bustins (2004, 2006 to account for those rainfall areas on the Iberian Peninsula which were not correlated with the NAOi. In addition, Camuffo et al (2006) recently used the WeMOi to compare it with variability in day-to-day pressure in Padova. In the study by Martin-Vide and Lopez-Bustins (2006), the WeMOi was shown to evolve in the opposite way to the AOi.…”
Section: Iberian Peninsula Winter Rainfall and Teleconnection Indicesmentioning
confidence: 99%
“…The WeMO represents an alternative definition for the Mediterranean Oscillation (MO) (Conte et al, 1989), but is focussed upon the western Mediterranean basin. Some studies have already used daily data in different teleconnection pattern indices (Baldwin and Dunkerton, 2001;Beniston and Jungo, 2002;Camuffo et al, 2006;Martin-Vide and Lopez-Bustins, 2006). The application of the WeMOi for finding weak surface pressure gradients for the occurrence of sea breezes must be defined on a daily scale.…”
Section: The Western Mediterranean Oscillation Index (Wemoi)mentioning
confidence: 99%
“…However, observations made with mercury barometers need several corrections based on the characteristics of the barometer, on the variations in temperature and on the latitude (e.g. Moberg et al, 2002;Camuffo et al, 2006). Unfortunately, in most cases the historical observations were registered without any correction, and it is usually very difficult, if not impossible, to find any information about the barometer.…”
Section: Introductionmentioning
confidence: 99%